2014
DOI: 10.1002/2014jd021626
|View full text |Cite
|
Sign up to set email alerts
|

Ambient CFCs and HCFC-22 observed concurrently at 84 sites in the Pearl River Delta region during the 2008-2009 grid studies

Abstract: Air samples were collected concurrently at 05:00 A.M. and 10:00 A.M. local Beijing time (geomagnetic time + 8) at 84 sites during two grid-study campaigns on 29 September 2008 and 1 March 2009 in the Pearl River Delta region, in order to offer snapshots of ambient CFCs and hydrochlorofluorocarbons (HCFCs) in different seasons and to indicate the presence of local emission sources. Compared to the subtropical northern hemisphere background levels, mean mixing ratios of CFC-11, CFC-12, CFC-113, CFC-114, and HCFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…Inter-comparisons of chemical analysis for CO, four halocarbons, and a total of 38 non-methane hydrocarbon (NMHC) species were conducted in laboratories of University of California, Irvine (UCI), Guangzhou Institute of Geochemistry (GIG) and Peking University (PKU) 17 , 21 , 30 . At PKU, air samples were concentrated using a three-stage cryofocusing pre-concentration system (Entech 7100, Entech Instruments, USA) and transferred into a gas chromatography–mass spectroscopy/flame ionization detector (GC-MS/FID) system for analysis (GC, HP-7890A; MSD, HP-5975C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-comparisons of chemical analysis for CO, four halocarbons, and a total of 38 non-methane hydrocarbon (NMHC) species were conducted in laboratories of University of California, Irvine (UCI), Guangzhou Institute of Geochemistry (GIG) and Peking University (PKU) 17 , 21 , 30 . At PKU, air samples were concentrated using a three-stage cryofocusing pre-concentration system (Entech 7100, Entech Instruments, USA) and transferred into a gas chromatography–mass spectroscopy/flame ionization detector (GC-MS/FID) system for analysis (GC, HP-7890A; MSD, HP-5975C).…”
Section: Methodsmentioning
confidence: 99%
“…Validations of emission inventories have been conducted using different top-down approaches, such as applying inverse modeling techniques to satellite retrieval 11 , 12 and ground-based observations 13 , as well as applying an emission ratio (ER) method to ground-level online measurements 14 , 15 and gridded measurements 16 , 17 . Satellite retrieval of glyoxal showed EI might underestimate aromatic emissions by a factor of 10–20 12 , while a recent study claimed there was a good agreement between the satellite retrievals and EI in the PRD 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) was measured from canister air samples by gas chromatography. 33 EF Calculations for Individual Refrigerants. The average EF of individual refrigerants from vehicles passing through the tunnel during a time interval T is calculated as follows: 31,32…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Field measurements of VOCs at background or remote locations remain scarce and sporadic in China. Several authors have reported VOC measurements at multiple sites, such as 45 cities in China for 2-5 days in January/February 2001 [Barletta et al, 2005], 84 sites in PRD for 4 days in -2009[Louie et al, 2013Zhang et al, 2014b], 14 sites in southeast China for 10 days in 2011 [Tong et al, 2013], and 27 sites in Beijing during 16 days from July 2009 to January 2011 [Wang et al, 2014b]. However, these data do not provide a complete picture of VOCs on a regional or national scale due to the limited number of sampling days.…”
Section: Introductionmentioning
confidence: 99%